Gait Kinematics After Taping in Participants With Chronic Ankle Instability - Chinn, Lisa (National Athletic Trainers Association, 2014)
CONTEXT: Chronic ankle instability is characterized by repetitive lateral ankle sprains. Prophylactic ankle taping is a common intervention used to reduce the risk of ankle sprains. However, little research has been conducted to evaluate the effect ankle taping has on gait kinematics. OBJECTIVE: To investigate the effect of taping on ankle and knee kinematics during walking and jogging in participants with chronic ankle instability. DESIGN: Controlled laboratory study. SETTING: Motion analysis laboratory. PATIENTS OR PARTICIPANTS: A total of 15 individuals (8 men, 7 women; age = 26.9 ± 6.8 years, height = 171.7 ± 6.3 cm, mass = 73.5 ± 10.7 kg) with self-reported chronic ankle instability volunteered. They had an average of 5.3 ± 3.1 incidences of ankle sprain. INTERVENTION(S): Participants walked and jogged in shoes on a treadmill while untaped and taped. The tape technique was a traditional preventive taping procedure. Conditions were randomized. MAIN OUTCOME MEASURE(S): Frontal-plane and sagittal-plane ankle and sagittal-plane knee kinematics were recorded throughout the entire gait cycle. Group means and 90% confidence intervals were calculated, plotted, and inspected for percentages of the gait cycle in which the confidence intervals did not overlap. RESULTS: During walking, participants were less plantar flexed from 64% to 69% of the gait cycle (mean difference = 5.73° ± 0.54°) and less inverted from 51% to 61% (mean difference = 4.34° ± 0.65°) and 76% to 81% (mean difference = 5.55° ± 0.54°) of the gait cycle when taped. During jogging, participants were less dorsiflexed from 12% to 21% (mean difference = 4.91° ± 0.18°) and less inverted from 47% to 58% (mean difference = 6.52° ± 0.12°) of the gait cycle when taped. No sagittal-plane knee kinematic differences were found. CONCLUSIONS: In those with chronic ankle instability, taping resulted in a more neutral ankle position during walking and jogging in shoes on a treadmill. This change in foot positioning and the mechanical properties of the tape may explain the protective aspect of taping in preventing lateral ankle sprains.